Consensus Guidelines on the Use of Intravenous Ketamine Infusions for Acute Pain Management From the American Society of Regional Anesthesia and Pain Medicine, the American Academy of Pain Medicine, and the American Society of Anesthesiologists - Schwenk, Eric S.; Viscusi, Eugene R.; Buvanendran, Asokumar; Hurley, Robert W.; Wasan, Ajay D.; Narouze, Samer; Bhatia, Anuj; Davis, Fred N.; Hooten, William M.; Cohen, Steven P. (Regional anesthesia and pain medicine, 2018)
BACKGROUNDKetamine infusions have been used for decades to treat acute pain, but a recent surge in usage has made the infusions a mainstay of treatment in emergency departments, in the perioperative period in individuals with refractory pain, and in opioid-tolerant patients. The widespread variability in patient selection, treatment parameters, and monitoring indicates a need for the creation of consensus guidelines. METHODSThe development of acute pain ketamine guidelines grew as a corollary from the genesis of chronic pain ketamine guidelines. The charge for the development of acute pain ketamine guidelines was provided by the Boards of Directors of both the American Society of Regional Anesthesia and Pain Medicine and the American Academy of Pain Medicine, who approved the document along with the American Society of Anesthesiologistsʼ Committees on Pain Medicine and Standards and Practice Parameters. The committee chair developed questions based on input from the committee during conference calls, which the committee then refined. Groups of 3 to 5 panel members and the committee chair were responsible for answering individual questions. After preliminary consensus was achieved, the entire committee made further revisions via e-mail and conference calls. RESULTSConsensus guidelines were prepared in the following areasindications, contraindications for acute pain and whether they differ from those for chronic pain, the evidence for the use of ketamine as an adjunct to opioid-based therapy, the evidence supporting patient-controlled ketamine analgesia, the use of nonparenteral forms of ketamine, and the subanesthetic dosage range and whether the evidence supports those dosages for acute pain. The group was able to reach consensus on the answers to all questions. CONCLUSIONSEvidence supports the use of ketamine for acute pain in a variety of contexts, including as a stand-alone treatment, as an adjunct to opioids, and, to a lesser extent, as an intranasal formulation. Contraindications for acute pain are similar to those for chronic pain, partly based on the observation that the dosage ranges are similar. Larger studies evaluating different acute pain conditions are needed to enhance patient selection, determine the effectiveness of nonparenteral ketamine alternatives, define optimal treatment parameters, and develop protocols optimizing safety and access to care.